Pendampingan Masyarakat Desa Larangan Panceng Gresik dalam Penguatan Pendidikat Literasi Digital - Fahrur Rosikh; M. Fathor Rohman; Muhammad Alim; Siti Nur Fauziyah4 (Bakti Insani: Jurnal Pengabdian dan Pemberdayaan, 2026)
Strengthening digital literacy is a crucial aspect in improving the quality of human resources in the era of digital transformation. This article aims to analyze the implementation of community mentoring activities in Larangan Village, Panceng District, Gresik Regency, to strengthen digital literacy education. The method used in this activity is a participatory approach through stages of socialization, training, and intensive mentoring for the community. The subjects of the activities include various levels of society, including students, youth, and adults. The material provided includes a basic understanding of digital literacy, the productive use of information technology, digital media ethics, and awareness of cybersecurity. The results of the activities show a significant increase in the community's understanding and skills related to the critical, selective, and responsible use of digital technology. In addition, there has been an increase in public awareness of the importance of maintaining personal data security and ethics in interacting in the digital space. Thus, this mentoring activity contributes to forming an adaptive, critical, and competitive society in the digital era